Maternal asthma and gestational diabetes mellitus: Exploration of potential associations. (March 2021) - Jensen, ME; Barrett, HL; Peek, MJ; Gibson, PG; Murphy, VE
Asthma and gestational diabetes mellitus are prevalent during pregnancy and associated with adverse perinatal outcomes. The risk of gestational diabetes mellitus is increased with asthma, and more severe asthma; yet, the underlying mechanisms are unknown. This review examines existing literature to explore possible links.  Asthma and gestational diabetes mellitus are associated with obesity, excess gestational weight gain, altered adipokine levels and low vitamin D levels; yet, it's unclear if these underpin the gestational diabetes mellitus–asthma association. Active antenatal asthma management reportedly mitigates asthma-associated gestational diabetes mellitus risk. However, mechanistic studies are lacking.  Existing research suggests asthma management during pregnancy influences gestational diabetes mellitus risk; this may have important implications for future antenatal strategies to improve maternal-fetal outcomes by addressing both conditions. Addressing shared risk factors, as part of antenatal care, may also improve outcomes. Finally, mechanistic studies, to establish the underlying pathophysiology linking asthma and gestational diabetes mellitus, could uncover new treatment approaches to optimise maternal and child health outcomes.